"I never felt like there was a place for me:" Experiences of Bisexual and Pansexual Individuals with a Christian Upbringing. Issue 2 (3rd April 2018) - Levy, Denise L.; Harr, Jennifer
ABSTRACT: Popular and scholarly literature describes the conflicts experienced by some gay and lesbian Christians, but less is known about the unique experiences of bisexual and pansexual populations. The purpose of this study was to understand the process by which bisexual and pansexual individuals with a Christian upbringing resolved conflict between sexual identity and religious beliefs. Grounded theory analysis of 17 interviews revealed a fluid and multidimensional process of resolution, which was influenced by community and relationships as well as experiences of isolation, secrecy, and shame. This study took place in the Bible Belt and was the first of its kind to explore the experiences of bisexual and pansexual individuals who continue to identify as Christian as well as those who have left their religion. It has implications not only for bisexual and pansexual individuals experiencing faith conflicts, but also for the faith leaders and helping professionals who support them.